Improvement of Subjective Olfactory Dysfunction in Chronic Rhinosinusitis With Nasal Polyps After Endoscopic Sinus Surgery - Ye, Ping; He, Shaojuan; Tang, Shuangmei; Xie, Xinyu; Duan, Chen; Zhang, Liqiang; Steinke, John W.; Borish, Larry; Li, Xuezhong; Feng, Xin (Frontiers in Surgery, 2022)
Objective: Olfactory impairment is a common complaint in patients with chronic rhinosinusitis with nasal polyps (CRSwNP), but the influence of endoscopic sinus surgery (ESS) on olfaction and the factors predicting olfactory impairment are not fully understood. This study aimed to assess the effect of ESS on improving olfactory dysfunction in patients with CRSwNP and to identify factors that predict prognosis. Methods: 56 patients with CRSwNP reported their self-evaluated olfactory dysfunction score preoperatively and 1 month, 3 months and 12 months after ESS. Preoperative clinical characteristics, computed tomography (CT) scan and sinonasal endoscopy examination were collected before surgery. Additionally, factors that predicted olfactory loss and affected improvement of olfaction after ESS were evaluated. Results: Olfactory improvement can be observed 1 month after ESS. A total of 73.2% (41/56) subjects experienced sustained recovery of subjective olfaction with the self-evaluated olfactory dysfunction score improving from 2.04 to 0.64 (P<0.001) after 12 months. The Lund-Mackay scores (r=0.593, P<0.001) and Lund-Kennedy scores (r=0.265, P<0.05) correlated with the preoperative olfactory dysfunction score. Multivariate logistic regression analysis revealed longer duration of olfactory dysfunction, blood eosinophilia, lower Lund-Mackay scores and peripheral distribution of CT opacification were risk factors that adversely affected recovery of olfactory function (P<0.05). Conclusion: ESS improved self-evaluated olfactory function in patients with CRSwNP. Lund-Mackay scores and Lund-Kennedy scores were correlated with olfactory function prior to surgery, while a longer course of the disease, higher blood eosinophilia, lower Lund-Mackay scores and peripheral distribution of CT opacification were risk factors for poor olfactory prognosis.